N-doped porous carbon@CNT nanowire as effective polysulfides adsorption-catalysis interlayer for high-performance lithium-sulfur batteries. (15th March 2023) - Yu, Xiaolei; Yin, Yan; Ma, Cheng; Xu, Jing; Qiao, Wenming; Wang, Jitong; Ling, Licheng
Graphical abstract: Highlights: The porous carbon coating can provide sufficient space for LiPSs capture via the physical entrapment. The CNT network as a conductive skeleton facilitates the electron/ion transportation. The presence of pyridinic N and pyrrolic N enhances the chemisorption capacity. Abstract: Lithium-sulfur (Li-S) batteries have received tremendous attention from the energy sector which have emerged as one of the most potential electrochemical energy storage systems. However, the annoying shuttle effect and sluggish polysulfides conversion process are still determining factor for hindering their large-scale practical applications. Herein, one-dimensional N-doped porous carbon@CNT nanowires (CNT@NC) were prepared as a trapping-catalyzing bifunctional interlayer for PP separator in Li-S battery. The linear structure of nanowires forms a continuous conductive network, which provides a fast transmission channel for Li + /e – . Moreover, the adsorption capability and catalytic conversion of polysulfides are enhanced by N doping. The resulting CNT@NC could effectively suppress the shuttle effect and improve the redox reaction kinetics. Therefore, the Li-S battery exhibits outstanding rate performance in addition to a high initial capacity of 1395.4 mAh g −1 and a long-time cycling life with a decay rate of only 0.025 % after 700 cycles at 0.5 C. This study furnishes a feasible scheme for the reasonable optimization of the Li-S battery interlayer and promotes electrochemical applications.